Rehabilitating Effect of Marijuana on Post-Covid-19 Pain Syndrome - Weinbroum, Avi A (Archives of Clinical and Medical Case Reports, 2022)
Post-COVID-19 syndrome is a condition that develops after the infected patient has recovered as evidenced by laboratory tests. It is characterized by persistence of physical symptoms and subjective sensations considered to be late effects of the virus on body functions. There are currently no therapeutic means to attenuate these symptoms without inducing adverse effects. A communication of the successful use of medical marijuana in a patient with post-COVID-19 syndrome is herein released.